(untitled) (Applied Biological Research, 2020)
A study was conducted to evaluate the effects of L-carnitine supplementation on serum lipid profile and antioxidant status of broilers fed with animal fat-based diet. Eighty days old straight run commercial broiler chicks (Vencobb) were randomly grouped into two treatment groups with four replications of ten chicks each. The rations were prepared with 5% animal fat. One group was supplemented with 900 mg L-carnitine kg-1 feed. The L-carnitine supplementation significantly reduced the serum cholesterol and LDL cholesterol levels; whereas serum triglyceride, HDL cholesterol and VLDL-cholesterol levels didn’t show any significant changes. The serum reduced-glutathione and superoxide dismutase concentrations were significantly higher in L-carnitine supplemented group. The study revealed that the supplementation of L carnitine not only improves the immune status but also decreases the serum cholesterol and LDL cholesterol level in broiler birds.